A prospective study of the predictors of mortality in acute exacerbation of COPD: an Indian perspective - Kamdar, Deepali J.; Patel, Dharmeshkumar (International Journal of Advances in Medicine, 2017)
Background: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality world-wide. In 2011, COPD was the third leading cause of death. The prevalence and burden of COPD are projected to increase over the coming decades due to continued exposure to COPD risk factors. Thus prevention, early detection and prompt treatment of COPD and it’s exacerbations may have an impact on the clinical progression and the risk of hospitalization. This is a prospective study to determine the predictors of mortality in COPD patients hospitalized for an acute exacerbation. Methods: This was a prospective study of 94 patients admitted for acute exacerbation of COPD in a tertiary care hospital over a period of 18 months. After a detailed medical history and physical examination, patient’s blood sample was sent for Arterial Blood Gas (ABG) analysis, a complete hemogram, blood sugar levels, serum albumin levels, blood urea nitrogen levels (BUN), serum creatinin levels, SGPT, SGOT and serum sodium and potassium levels. We then compared these parameters in patients who died with those who survived to determine the mortality predictors. Results: A statistically significant relation was obtained between male gender, smoking history (odd ratio of 1.5), number of pack years (p = 0.029), history of prior admission (odds ratio of 2), longer duration of illness (p = 0.045), elevated blood sugar levels (p = 0.035), hypoalbuminaemia (0.001), hypopnatremia (0.001), respiratory acidosis (0.003), elevated partial pressure of CO2 (0.001) and mortality. Conclusions: We found a male preponderance, with increase in mortality with the increase in the number of smoking pack years. Longer duration of illness was also an important predictor of mortality. Respiratory acidosis, hyponatremia, elevated blood sugar levels and hypoalbuminemia at the time of presentation were other important predictors of mortality in patients hospitalized for acute exacerbation of COPD.